Robust Control Frameworks for Heave Disturbance Suppression in Offshore Managed Pressure Drilling Environments - Atif Rehman; Rimsha Ghias; Iftikhar Ahmad; Hammad Iqbal Sherazi (IEEE Access)
Managed Pressure Drilling (MPD) systems have transformed drilling operations by enabling precise wellbore pressure control, particularly in challenging conditions. Automatic MPD, leveraging advanced choke valve mechanisms, effectively mitigates pressure fluctuations caused by drill string oscillations induced by Heave Motion. This study introduces advanced nonlinear control strategies, including Sliding Mode Control (SMC) and Super-Twisting Sliding Mode Control (STSMC), to enhance pressure regulation. Controller gains are optimized using an improved Grey Wolf Optimization algorithm, targeting the minimization of the Integral Time Absolute Error. Stability of the controllers is rigorously analyzed through Lyapunov criteria. Comprehensive performance evaluations via MATLAB/Simulink simulations, complemented by real-time validation using a C2000 Delfino MCU F28379D Launchpad, demonstrate the robustness and efficacy of the proposed control methodologies.